Job Satisfaction in Education Sector of Megacities: A Study of Higher Secondary Institutions of Karachi (Al-Qamar, 2024)
Megacities have been centering of attraction for their modernity, growth and opportunities, whereas they combat with number of challenges like overcrowding, high cost of living, increased competition etc. Similarly, megacity Karachi (biggest metropolitan city of Pakistan, ranked as 7th most populous city in the world, with the growth rate of 2.41%, 2020), which makes it quite apparent that managing in this mega city do makes it challenging on individual level as well. Every megacity depends upon industries and organizations for its growth and Education sector is one of those key players, where Higher Secondary Education Institutions are considered as backbone in employing more of skilled workers. Job satisfaction is the main predictor of organizational success. This paper examined the factors affecting the job satisfaction in Higher Secondary Educational Institutions of Karachi. The data were collected through primary data gathering using questionnaire for employees working in public and private colleges of megacity Karachi. Sample size is restricted to 100 respondents selected through convenient sampling. This research was aimed at finding relationship between employees’ job satisfaction in Higher Secondary Education Institution of Megacity (Karachi) and its dynamics. In final part of this research, we tried to find out relationship between level of job satisfaction and demands of the megacity, exploring factors affecting job satisfaction in megacities.
Keywords: Job satisfaction; organizational learning; employee motivation; work environment; city dynamics